2007
DOI: 10.1002/qua.21392
|View full text |Cite
|
Sign up to set email alerts
|

β‐Aminoacrolein: An ab initio, AIM and NBO study

Abstract: ABSTRACT:The molecular structure and the intramolecular hydrogen bonding of ␤-aminoacrolein and its simple derivatives were investigated at the MP2 and B3LYP levels of theory using the standard 6-311ϩϩG(d, p) basis set. The "atoms in molecules" or AIM theory of Bader which is based on topological properties of the electron density (), was used. Additionally, an analysis of the critical points was performed to study the nature hydrogen bonding in these systems. Natural bond orbital (NBO) analysis was also carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…It is important to note that the B3LYP method is a method of choice for calculating properties discussed in this work. For calculations involving conformational preferences (such as the stronger intramolecular HB in ClAA compared to AA) it has been shown that in several cases 2, 10 the B3LYP method yields qualitative agreements to experiment. We have compared the results of these calculations to those obtained by other density functional theory (DFT) methods (i.e., PW91, PBE, HCTH, BOP) as well as local density approximation (LDA) methods (i.e., VWN, PWC).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the B3LYP method is a method of choice for calculating properties discussed in this work. For calculations involving conformational preferences (such as the stronger intramolecular HB in ClAA compared to AA) it has been shown that in several cases 2, 10 the B3LYP method yields qualitative agreements to experiment. We have compared the results of these calculations to those obtained by other density functional theory (DFT) methods (i.e., PW91, PBE, HCTH, BOP) as well as local density approximation (LDA) methods (i.e., VWN, PWC).…”
Section: Resultsmentioning
confidence: 99%
“…Along this line of research, attention has been paid to β‐diketones 1, which are useful chelating agents for transition metal ions. Such complexes include platinum, iridium, gold, mercury, and copper 2–4. It is of practical and theoretical importance to investigate keto–enol equilibria which can take place in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the B3LYP method is a method of choice for calculating properties discussed in this work. For calculations involving conformational preferences (such as the stronger intramolecular HB in ClAA compared to AA) it has been shown that in several cases [2,10] the B3LYP method yields qualitative agreements to experiment. We have compared the results of these cal- Calculated using the 6-31G** basis set.…”
Section: Geometrical Parametersmentioning
confidence: 92%
“…Delocalization effects can be identified from the presence of off-diagonal elements of the Fock matrix in the NBO basis used. The strength of these delocalization interactions, E (2) , are estimated by second order perturbation theory which are in kcal mol…”
Section: Geometrical Parametersmentioning
confidence: 99%
See 1 more Smart Citation